LONG-TERM INTRAOCULAR PRESSURE AFTER UNCOMPLICATED PARS PLANA VITRECTOMY FOR IDIOPATHIC EPIRETINAL MEMBRANE. Issue 1 (January 2019) - Tognetto, Daniele; Pastore, Marco R.; Cirigliano, Gabriella; D'Aloisio, Rossella; Borelli, Massimo; De Giacinto, Chiara
Abstract : Purpose: To investigate long-term intraocular pressure trends after uncomplicated pars plana vitrectomy for idiopathic epiretinal membrane. Methods: Three hundred and sixty-eight eyes of 368 consecutive patients were enrolled. Changes in intraocular pressure 1, 3, 6, and 12 months after surgery and during the final follow-up visit were evaluated in vitrectomized eyes and nonvitrectomized fellow eyes. Results: The median follow-up period was 36 months (range 12–92 months). Longitudinal data analysis evidenced a 2.5-mmHg (2.2 mmHg; 2.7 mmHg, 95% confidence interval) statistically significant difference in intraocular pressure 30 days after surgery between treated and fellow untreated eyes, gradually recovering to a not significant 0.2-mmHg (−0.1 mmHg; 0.4 mmHg, 95% confidence interval) difference within 26 months. The incidence of late-onset ocular hypertension was 5.7% (21 over 347, 2%; 12%, 95% confidence interval) without difference between the treated eyes and the group control. No significant difference in the incidence of late-onset ocular hypertension and sex, lens status, or gauge of vitrectomy instruments was detected. Only patient's age was significantly higher (mean difference 4.2 years; 0.1–8.0 years, Monte Carlo, 95% confidence interval) in those who developed late-onset ocular hypertension in the vitrectomized eye. Conclusion: Uncomplicated pars plana vitrectomy for idiopathic epiretinal membrane seems not to increase the risk of late-onset ocular hypertension or open-angle glaucoma development. Abstract : The authors' analysis of data from 368 consecutive eligible eyes with idiopathic epiretinal membrane after uncomplicated pars plana vitrectomy revealed no increased risk of late-onset ocular hypertension or open-angle glaucoma development.